Kejadian Stres Kerja Pada Petugas Laboratorium Di Rumah Sakit X Menggunakan Dass 42 Tahun 2023 - Kusumawati, Utari; Irfandi, Ahmad; Utami, Desyawati; Azteria, Veza (Journal of Natural Sciences, 2024)
Work stress experienced by laboratory officers in hospitals could have been influenced by various factors, including limited human resources that encouraged multiple roles for each laboratory officer. This could increased the risk of other mental health disorders. The purpose of this study was to determine the incidence of work stress in laboratory officers at Hospital X. This research method was quantitative descriptive research. The sampling technique used in this study was total sampling with total sample size of 17 laboratory officers at Hospital X. This study used the DASS 42 questionnaire. The primary data was processed using univariate analysis to determine the distribution and frequency of data. The findings of this study revealed that the majority of laboratory officers at Hospital X had experienced moderate levels of depression, namely 5 respondents (29.4%). Regarding anxiety levels, the majority of laboratory officers at Hospital X experienced moderate and severe levels of anxiety, with 5 respondents each (29.4%). The majority of Hospital X laboratory officers experienced moderate and normal level of stress, with 5 respondents each (29.4%). It is hoped that hospital management could consider adding human resources and providing facilities and infrastructure to minimize the risk of work stress.